Дослідження впливу режимних факторів на кінетику процесу дегідратації заліза (II) сульфат гептагідрату фільтраційним методом - Кіндзера, Д. П.; Кочубей, В. В.; Атаманюк, В. М.; Цюра, Н. Я.; Гелеш, А. Б.; Kindzera, D. P.; Kochubei, V. V.; Atamanyuk, V. M.; Tsiura, N. Y.; Helesh, A. B. (Видавництво Львівської політехніки, 2023)
Запропоновано фільтраційний метод постадійної дегідратації заліза (ІІ) сульфат гептагідрату. На основі узагальнення експериментальних даних гідродинаміки процесу, отримано розрахункову залежність, що дає змогу теоретично визначати втрати тиску у стаціонарному шарі FeSO4∙7H2O. За результатами комплексного термічного аналізу, встановлено закономірності протікання процесу дегідратації FeSO4∙7H2O в різних температурних інтервалах. Для реалізації дегідратації FeSO4∙7H2O, з відщепленням перших трьох молекул кристалізаційної води, обрано температуру 339 К, яка забезпечує збереження кристалічного стану продукту. Досліджено кінетику видалення вологи з FeSO4∙7H2O за різних висот шару матеріалу та швидкостей руху теплового агенту. На основі проведених розрахунків енергозатрат, встановлено оптимальні параметри процесу: висоту стаціонарного шару H = 60.10-3м та фіктивну швидкість руху теплового агенту v0 = 0,86 м/с.

The filtration method of gradual dehydration of iron (II) sulfate heptahydrate hase been proposed. Based on the generalization of experimental data of hydrodynamics, the calculated dependence was obtained, which makes it possible to determine theoreticallypressure losses in the stationary layer of FeSO4∙7H2O. According to the results of complex thermal analysis, the regularities of the gradual dehydration process of FeSO4∙7H2O have been established in different temperature intervals. The temperature of 339 K has been chosen, to implement the FeSO4∙7H2O dehydration process with the separation of the first three molecules of crystallization water, ensuring the preservation of the crystalline state of the product. The kinetics of moisture removal from FeSO4∙7H2O at different heights of the material layer and velocities of heat agent movement have been investigated. Based on energy consumption calculations, the optimal parameters of the process were established: the height of the stationary layer H = 60.10-3mand the fictitious velocities of the heat agent movement v0 = 0,86 m/s.
Study of the influence of regime factors on the kinetics of the dehydration process of iron (ii) sulfate heptahydrate using the filtration method
Keywords: заліза (ІІ) сульфат гептагідрат; залізоокисні пігменти; процес дегідратації; тепловий агент; стаціонарний шар; кристалізаційна вода; термічний аналіз; iron(II) sulfate heptahydrate; iron oxide pigments; dehydration process; heat agent; stationary layer; crystallization water; thermal analysis